On the Research of Paradigms in Linguistics - Makhsudova , Nilufar Abdurasulovna (The Lingua Spectrum, 2026)
The scientific article systematically examines the historical stages of the formation of linguistic science and the processes of fundamental scientific paradigm shifts. It is argued that the development of linguistics is not simply a change in theories, but a fundamental transformation of attitudes towards language. The study analyzes the emergence of traditional comparative-historical linguistics, its role in determining the genetic relationship of languages, and the characteristics of the formation of structural linguistics (immanent linguistics), which views language as an internal system. The main part of the article is devoted to the modern linguistic paradigm that emerged as a result of the “anthropocentric turn” in the late 20th and early 21st centuries. The author scientifically demonstrates the necessity of transitioning from classical approaches, which study language in isolation from the human factor, to a modern methodology that analyzes it in an inseparable connection with human consciousness, culture, and social activity. Specifically, the article provides a comparative analysis of the core principles of priority areas in modern linguistics: cognitive linguistics, linguoculturology, and pragmalinguistics. In the course of the research, such principles as interdisciplinary integration, communicability, anthropocentrism, functionalism, and explanatarity are highlighted, and new scientific directions at the intersection of linguistics with psychology, culturology, and sociology are analyzed. The conclusions put forward by the author can contribute to a deeper understanding of the theoretical issues of linguistics, the identification of trends in modern language development, and the strengthening of the methodological framework of philological research.